Tiptoeing the Line Between National Security and Protectionism: A Comparative Approach to Foreign Direct Investment Screening in the United States and European Union. (2019) - Jacobs, Jason
Abstract: Weaponization of state-backed, foreign investments by China is an emerging national security threat in the United States and the European Union. The U.S. and E.U. have espoused similar policy goals—to address the threat without closing their markets to foreign direct investment—while fostering increased cooperation between allied partners in screening transactions. On the surface, the recent, China-specific measures taken by the U.S. and the investment screening framework adopted by the E.U. appear reflective of an alignment of those policy goals. Indeed, many commentators have suggested that is exactly what is happening. However, closer examination reveals a stark divergence. The U.S. has a robust screening mechanism that has evolved into a weapon of economic warfare. The E.U. meanwhile, remains a patchwork of conflicting—or nonexistent—national regulations overlaid by a comparatively toothless investment screening framework. There is a tendency to attribute this divergence to structural differences between the United States and European Union. This in-depth comparison of U.S. and E.U. investment screening mechanisms exposes a split that goes beyond application and into actual policy. This revelation should temper expectations that the E.U. is equipping itself to block transactions that are of concern to the U.S.